Urban regeneration. Benefits of nature-based solutions - Katia Perini; Francesca Mosca; Andrea Giachetta (Agathón)
Today’s urban environment features several critical issues related to what in Italy is called ‘cementification’: among the main ones, the phenomenon of heat islands, the cause of several problems related to citizens’ health, especially for the weaker population groups such as children and elderly people. This paper presents the results of a research focused on identifying a combination of nature-based solutions, offering good benefits both from the point of view of improving microclimate comfort and from the point of view of psychological comfort for the people who will use the regenerated areas.